Dialogamos sobre el cuidado de nuestro espacio personal - Gutierrez Contreras, Merli Aguedita (2019)
The present work is especially focused on students knowing, valuing and taking care of their personal space, conceptualizing personal space as that space that surrounds the person and that allows them to interact with other people in a comfortable and appropriate way to the circumstances._x000D_ In fact, every person has other inner spaces – of intellectual or emotional value -, that treasures with certain affection. This work intent to deepen on the expansion of the concept of personal space and its role in three interpersonal communication scenarios: the willingness to expose one’s own personal space; the receptivity to the personal space of others; and the entrance into the personal space of others._x000D_ The development of this learning class has taken into consideration the educational processes of a class in order to promote the active and meaningful participation of students using a list of a check table to verify the purpose of the new learning.